Heterozygous Pathogenic Variant in DACT1 Causes an Autosomal‐Dominant Syndrome with Features Overlapping Townes–Brocks Syndrome. Issue 4 (2nd February 2017) - Webb, Bryn D.; Metikala, Sanjeeva; Wheeler, Patricia G.; Sherpa, Mingma D.; Houten, Sander M.; Horb, Marko E.; Schadt, Eric E.
Abstract : A heterozygous nonsense variant in DACT1 was identified by whole exome sequencing to cause imperforate anus, structural renal abnormalities, genitourinary abnormalities, and/or ear anomalies. Functional studies, including in vivo studies in Xenopus, provided support that DACT1 is causative of a specific genetic syndrome. ABSTRACT: A heterozygous nonsense variant was identified in dapper, antagonist of beta‐catenin, 1 ( DACT1 ) via whole‐exome sequencing in family members with imperforate anus, structural renal abnormalities, genitourinary anomalies, and/or ear anomalies. The DACT1 c.1256G>A;p.Trp419 * variant segregated appropriately in the family consistent with an autosomal dominant mode of inheritance. DACT1 is a member of the Wnt‐signaling pathway, and mice homozygous for null alleles display multiple congenital anomalies including absent anus with blind‐ending colon and genitourinary malformations. To investigate the DACT1 c.1256G>A variant, HEK293 cells were transfected with mutant DACT1 cDNA plasmid, and immunoblotting revealed stability of the DACT1 p.Trp419 * protein. Overexpression of DACT1 c.1256G>A mRNA in Xenopus embryos revealed a specific gastrointestinal phenotype of enlargement of the proctodeum. Together, these findings suggest that the DACT1 c.1256G>A nonsense variant is causative of a specific genetic syndrome with features overlapping Townes–Brocks syndrome.